La familia en salud mental: ayuda para el cuidado clínico de enfermería - Silva, Kely Vanessa Leite Gomes da (2011)
This is a theoretical reflection on the clinical nursing care in mental health that is offered to the family. In view of having a family member with mental suffering, the family would delegate the care to that relative to the mental institution, thus there should be collaboration between the nursing and medical team to organize the environment and ensure family and social isolation. With the Psychiatric Reform, based on the proposal for psychosocial care, the family becomes the center of attention for health care professionals. The necessary support for clinical nursing care includes making conceptual changes in implementing health education, interdisciplinary work, and in the broadened clinic, so as to ensure comprehensiveness and subjects' autonomy. Clinical nursing care should permeate the subjects' politicalization, in which the actors militate to reach autonomy, and the practices involve dignity, creativity, welcoming, interdisciplinarity, hearing, and knowledge sharing.